Effect Of Consideration Of Seismic Design On Cost Increase Of Regular Layout Reinforced Concrete High Rise Buildings In Penang Island - Daniel, Lim Wei Ping (Universiti Sains Malaysia, 2022)
Since Malaysia is not situated in an area with active seismic faults, the majority of its structures were designed in accordance with Eurocode 2 and MS 1553:2002, which does not include any seismic provisions. However, the development of Malaysian National Annex (NA) to Eurocode 8 has provided a design guideline to check the ability of the existing buildings that were designed without considering seismic load to satisfy the design requirements. This study is aimed at determining the variation in material cost considering the effect of seismic load in the design. The influence of three ground type and three different number of storeys building on material cost was considered. A total of 12 analysis models was carried out by EtabsV18 with storey height of 35 storey, 40 storey and 45 storey with and without the consideration of seismic effect on ground types A, D, and E. The material cost increment between seismic design and non-seismic design was determined. Furthermore, the material cost increment of models considering seismic design on different ground types was also determined. The models of reinforced concrete building were designed based on EC 2 and redesigned according to EC 8 with peak ground acceleration, αgR 0.06g reflecting the low seismic zone for ductility class low (DCL) including the common ground type A, D and E in Penang. In comparison with EC8, the provision of reinforcement bar according to EC2 is higher for every storey height investigated. The percentage of cost increment for seismic design models are found as negative percentage values for 35 storey, 40 storey and 45 storey buildings. Besides, when comparing with ground type D, the material cost for ground type A are -1.344%, -1.229% and -1.365% for 35 storey, 40 storey and 45 storey buildings, respectively. In comparison with ground type D, the material cost for ground type E does not show significant differences for 35 storey, 40 storey and 45 storey buildings, respectively.